The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/infdis/jiz401
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Human Papillomavirus (HPV) Lineage and Sublineage Variant Pseudoviruses to Neutralization by Nonavalent Vaccine Antibodies

Abstract: Natural variants of human papillomavirus (HPV) are classified into lineages and sublineages based upon whole-genome sequence, but the impact of diversity on protein function is unclear. We investigated the susceptibility of 3–8 representative pseudovirus variants of HPV16, HPV18, HPV31, HPV33, HPV45, HPV52, and HPV58 to neutralization by nonavalent vaccine (Gardasil®9) sera. Many variants demonstrated significant differences in neutralization sensitivity from their consensus A/A1 variant but these were of a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Among the four HPV16 lineages, lineage D contained the largest number of different glycosylation sites in L1 and L2 proteins from lineage A ( Figure 2 ). Godi et al showed that compared with HPV16 lineage A, lineages B, C, and D exhibited slightly (<2-fold) reduced sensitivity to nonavalent vaccine sera [ 62 ]. The unique glycosylation sites existing on the L1 proteins of lineages B, C and D, especially D, might be one of the determinants accounting for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Among the four HPV16 lineages, lineage D contained the largest number of different glycosylation sites in L1 and L2 proteins from lineage A ( Figure 2 ). Godi et al showed that compared with HPV16 lineage A, lineages B, C, and D exhibited slightly (<2-fold) reduced sensitivity to nonavalent vaccine sera [ 62 ]. The unique glycosylation sites existing on the L1 proteins of lineages B, C and D, especially D, might be one of the determinants accounting for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Among the four HPV16 lineages, lineage D contained the largest number of different glycosylation sites in L1 and L2 proteins from lineage A (Figure 1). Godi et al showed that comparing with HPV16 lineage A, lineage B, C, and D exhibited slightly (<2-fold) reduced sensitivity to nonavalent vaccine sera [57]. The unique glycosylation sites existed on the L1 proteins of lineages B, C and D, especially D, might be one of the determinants for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of cross-protection against HPV types that belong to both the same and different α-species was also seen for HPV16 and HPV18 in vaccinated women from Costa Rica (Skinner et al, 2016), where HPV31 (α-9) and HPV51 (α-6) infections appeared post-vaccination. Moreover, considering that sublineage variants show significant differences in neutralization sensitivity (Godi et al, 2015;Godi et al, 2019), we examined HPV81 strains, to investigate whether different L1 antigenic variants were present in SI and MI, and whether they might influence their cross-protection properties. Overall, the L1 protein harbored a greater number of variable amino acids than the L2 protein (35 amino-acid vs 9 aminoacid changes, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…β-Turns are very frequently the sites of interactions in proteins and peptides, both because they are topologically biased to occur on the surfaces of proteins, and because their structures present the side chains of corner residues, which are optimal for molecular recognition. The Hamming distance (Hamming, 1986;Farci et al, 2000) was calculated using online software (Hacksparrow, 2019). The Pearson distance and phylogenetic tree were calculated using the MEGA10 software (Kumar et al, 2018).…”
Section: L1 and L2 Sequencesmentioning
confidence: 99%